Comparação imunoistoquímica e citomorfométrica entre células gigantes multinucleadas e fungos em lesões orais por paracoccidioidomicose - Pedreira, Renato Do Prado Gomes (2015)
Multinucleated giant cells (MGC) are considered to be a hallmark of granulomatous inflammation; thus they may play an essential role in the host response against pathogens, particularly Paracoccidioides brasiliensis. This study characterizes the MGC found in oral chronic paracoccidioidomycosis and assesses their correlation with the amount of fungi within oral tissues. Twenty-six cases were included. They were classified as loose or dense granulomas and the total MGC, including foreign-body and Langhans giant cells, besides the total and intracellular fungi were taken into consideration. CD163 immunoexpression was performed and CD163+ multinucleated giant cells were also quantified. Our results showed that dense granulomas revealed more foreign-body type and total giant cells than loose granulomas (P < 0.05). Total giant cells showed a positive linear correlation with the CD163+cells (P = 0.003; r = 0.56) and intracellular fungi quantification (P = 0.045; r = 0.40). Oral chronic paracoccidioidomycosis lesions contain MGC that mainly belong to a CD163+ phenotype, also showing both Langhans and foreign-body arrangements; such CD163+/M2 profile may sustain the chronic form and persistence of PCM oral lesions; additionally, the higher the presence of MGC, the higher the amount of phagocyted fungi, evidencing that such kind of giant cells are indeed able to perform phagocytosis.